Using extensive reading to improve English reading comprehension of Year 6 students and their perceptions towards the intervention - Seyapalan, Evanna Devi; Loo, Kien Men; Abd Rahman, Nur Fatin Nabila (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
This study aims to identify the perceptions of Year 6 students towards extensive reading strategy to improve their English reading comprehension. From observation and experience of teaching, although reading strategies were explicitly taught to achieve reading comprehension, students still go through major difficulties in understanding a text. In this proposed study, the respondents are 37 Year 6 students from a school in Damansara. Selected via purposive sampling, a pre-test will be administered to the students prior to the intervention of extensive reading for 5 months. At the end of the intervention, post-test will be given to assess whether there is any improvement in their reading comprehension, followed by the administration of the survey questionnaire on their perceptions. Instruments such as extensive reading approach, past years UPSR English comprehension paper, Student Perception of Extensive Reading Questionnaire and semi-structured interview will be used to collect the data needed for the proposed study.